2023
DOI: 10.3390/en16247963
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Analysis on Compression-Assisted Adsorption Chiller Using Chlorides for Underground Cold Transportation

Meng Yu,
Suke Jin,
Wenyun Zhang
et al.

Abstract: Thermal-driven refrigeration technologies, e.g., absorption- or adsorption-type, are gathering momentum since they can utilize low-grade heat from industrial, solar or geothermal energy. However, heat sources and end users are usually mismatched, which could lead to potential heat pollution and increased carbon emissions. Long-distance thermal energy transportation is good for district heating and cooling, which is of great significance if it can achieve a high energy-transportation density and low heat loss. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…The studies on the ADS for ice production reported COP ranged from 0.452 to 0.086 [14]. A recent strategy to increase the benefits of both systems (the VCS and ADS) and lessen their drawbacks has been offered in the literature by integrating the two systems using different approaches [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The studies on the ADS for ice production reported COP ranged from 0.452 to 0.086 [14]. A recent strategy to increase the benefits of both systems (the VCS and ADS) and lessen their drawbacks has been offered in the literature by integrating the two systems using different approaches [15][16][17].…”
Section: Introductionmentioning
confidence: 99%